Generation of a conditional knockout allele for the NFAT5 gene in mice - Küper, Christoph; Beck, Franz-Xaver; Neuhofer, Wolfgang (Frontiers in Physiology, 2015)
The osmosensitive transcription factor nuclear factor of activated T-cells 5 (NFAT5), also known as tonicity enhancer element binding protein (TonEBP) plays a crucial role in protection of renal medullary cells against hyperosmotic stress, urinary concentration, the adaptive immune response, and other physiological systems. Since it is also important for development, conventional homozygous-null mutations result in perinatal death, which hinders the analysis of NFAT5 function in specific tissues in vivo. Here we describe the generation of mice with a conditional-null allele, in which loxP sites are inserted around exon 4. Mice harboring the floxed allele (NFAT5flx) were mated to a strain expressing a tamoxifen-inducible derivative of the Cre-recombinase (Cre+) under the control of the ubiqitinC promoter. The resultant homozygous conditional knockout mice (Cre+ NFAT5flx/flx) are viable, fertile, and show normal expression of NFAT5 and NFAT5 target genes, indicating that the conditional alleles retain their wild-type function. Induction of Cre-mediated recombination by administration of tamoxifen in 8-week-old mice resulted in a decrease in NFAT5 expression of about 70-90% in all tested tissues (renal cortex, renal outer medulla, renal inner medulla, heart, lung, spleen, skeletal muscle). Accordingly, the expression of the NFAT5 target genes aldose reductase and heat shock protein 70 in the renal medulla was also significantly decreased. Mice harboring this conditional knockout allele should be useful in future studies for gaining a better understanding of tissue and cell-type specific functions of NFAT5 in adult animals under physiological and pathophysiological conditions.